The Effect of Brand Evaluations towards Intention to stay at 5 stars hotel with Social Media Influencer as a Moderating Variable. - Susilo, Clarissa Listya; Utomo, Hendra (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2021)
Covid-19 pandemic has wreaked havoc in indonesia's economy, especially in its tourism sectors. Marketing research in tourism and hospitality industry can help to recovier the tourism and hospitality sectors by providing insights about people's motivation to visit or travel to a certain place, stay at a certain establishments or buy a certain things. This research aims to understand what motivates people to want to stay at a 5 stars hotel in Bali and whether Social Media Influencers (SMI) has amoderating effect towards intention to stay at a 5 stars hotel in Bali.This research uses a non-probability sampling method with purposive sampling as its sampling technique. total number of respondents used in this research is 100. This research uses a path analysis from SEM-PLS application. Based on results from this research in can be concluded that attitude towards the brand and brand image don’t have a significant effect towards intention to stay at a 5 stars hotel. While brand trust has a significant effect towards intention to stay at a 5 stars hotel. As for the moderating effect of SMI, this research found that SMI doesn’t has a moderating effect in the relationship between brand evaluation (brand trust, brand image and attitude towards the brand) and intention to stay at the hotel. Although this research finds that there are a significant effect between SMI as an independent variable towards intention to stay at the hotel.